Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve by substitution 3x - 5y = -1 , x-y = -1

Sagot :

Answer:

(-2, -1)

Step-by-step explanation:

first you must reorganize the equations so that one of them has x or y equaling to something

x - y = -1 --> x = y - 1

then substitute that in for x

3(y - 1) - 5y = -1

and solve for y

3y - 3 - 5y = -1

-2y = 2

y is -1

then plug it back in to an equation to find x

x + 1 = -1

x is -2